A Bottom-Up Approach to Encouraging Sustained User Adoption of a Secure Text Messaging Application - Tsega, Surafel; Kalra, Angeli; Sevilla, Cesar T.; Cho, Hyung J. (Applied Clinical Informatics, 2019)
Background Inpatient providers are increasingly utilizing alternative communication modalities outside what has traditionally been used, including short messaging service text messaging and application-based chat tools. Text messaging that meets the recommendations of the Joint Commission (“secure text messaging”) allows for the communication of sensitive patient information through an encrypted platform.Objective In this quality initiative utilizing the Plan-Do-Study-Act (PDSA) model, we attempted two rollout designs to maximize user adoption of a secure text messaging application.Methods Our institution launched a secure text messaging application (Cureatr) using a top-down approach during the first PDSA cycle, defined as communication and outreach through department chairs and administrative leaders throughout the hospital. After inadequate user adoption, we transitioned to a bottom-up approach in the second PDSA cycle, defined as direct communication and engagement with end users. This campaign targeted the hospital medicine and inpatient social work department, and used discharge planning as a use case to encourage adoption.Results Over a 6-month period, we observed an increase in active users in the hospital medicine department (7.5 unique users per month to 29 users during the first and second PDSA cycles, p < 0.01). Additionally, we saw an increase in messages sent and received by the medicine (687 messages on average per month and 7,367 messages per month in each respective PDSA cycle, p < 0.01) and social work departments (350 messages on average per month and 6,083 messages during the first and second PDSA cycle, p < 0.01). We did not observe a significant change in active users or messages sent in the surgery department, which did not participate in the second PDSA cycle.Conclusion We believe that a bottom-up approach is important to introducing mobile applications to the inpatient setting and can contribute to sustained user adoption.
Keywords: hospital communication systems; secure text messaging; smartphone; confidentiality; mobile applications